2013
DOI: 10.1186/2052-1847-5-11
|View full text |Cite
|
Sign up to set email alerts
|

The association between functional movement and overweight and obesity in British primary school children

Abstract: BackgroundThe purpose of this study was to examine the association between functional movement and overweight and obesity in British children.MethodsData were obtained from 90, 7–10 year old children (38 boys and 52 girls). Body mass (kg) and height (m) were assessed from which body mass index (BMI) was determined and children were classified as normal weight, overweight or obese according to international cut offs. Functional movement was assessed using the functional movement screen.ResultsTotal functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(114 citation statements)
references
References 31 publications
(60 reference statements)
7
93
4
2
Order By: Relevance
“…It is possible that when children feel confident in their skills, they tend to engage in higher levels of physical activity (Gabbard, 2011). Positive relationships have also been found between FMS performance and weight status (Castetbon & Andreyeva, 2012;Duncan, Stanley, & Wright, 2013) among young children. Further, research has pointed out that children who stay active tend to maintain high levels of physical fitness (Barnett, van Beurden, Morgan, Brooks, & Beard, 2008;Mitchell et al, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…It is possible that when children feel confident in their skills, they tend to engage in higher levels of physical activity (Gabbard, 2011). Positive relationships have also been found between FMS performance and weight status (Castetbon & Andreyeva, 2012;Duncan, Stanley, & Wright, 2013) among young children. Further, research has pointed out that children who stay active tend to maintain high levels of physical fitness (Barnett, van Beurden, Morgan, Brooks, & Beard, 2008;Mitchell et al, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…In one of the rare UK studies, albeit with 7-10 year olds, a study by Duncan et al (2013) reported no gender differences in motor proficiency when considered as total scores, but girls outperformed boys on the hurdle step and straight leg raise with boys outperforming girls on the trunk stability push-up. Other studies have reported varying and often conflicting perspectives on the significance of gender in motor proficiency when studying preschool children (Bala & Katić, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, increasing BMI category and obesity are highly associated with multiple morbidity, cardiovascular disease and type-2 diabetes mellitus which in turn are major causes of morbidity and mortality in the industrialized world 30 . Obesity is also associated with poorer functional movement 32 and is well established as a risk factor for OA 33 .…”
Section: Bmimentioning
confidence: 99%